1993
DOI: 10.1016/s0022-5347(17)36003-2
|View full text |Cite
|
Sign up to set email alerts
|

Orchiectomy and Nilutamide or Placebo as Treatment of Metastatic Prostatic Cancer in a Multinational Double-Blind Randomized Trial

Abstract: The efficacy and tolerance of the nonsteroidal antiandrogen nilutamide in the treatment of prostatic cancer were studied in a large double-blind clinical trial initiated in 1986. Patients with metastatic prostatic cancer without prior endocrine manipulation underwent orchiectomy and were randomized to 1 of 2 groups receiving nilutamide (225 patients) or placebo (232). Nilutamide and placebo were evaluated for efficacy in 207 and 216 patients, respectively. Progression-free survival was significantly longer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(95 citation statements)
references
References 17 publications
2
89
0
4
Order By: Relevance
“…11 There is a continuing debate regarding the clinical value of this combined hormonal therapy. The National Cancer Institute (NCI) study 0036, 11 European Organization for Research and Treatment of Cancer (EORTC) study 30853, 12 Canadian Anandron study, 13 and Multinational Nilutamide Study 14 all showed a survival benefit of 7-15 months with combined hormonal therapy. Other studies, however, have not supported this finding.…”
Section: Primary Hormonal Therapy Sg Koff Et Almentioning
confidence: 99%
“…11 There is a continuing debate regarding the clinical value of this combined hormonal therapy. The National Cancer Institute (NCI) study 0036, 11 European Organization for Research and Treatment of Cancer (EORTC) study 30853, 12 Canadian Anandron study, 13 and Multinational Nilutamide Study 14 all showed a survival benefit of 7-15 months with combined hormonal therapy. Other studies, however, have not supported this finding.…”
Section: Primary Hormonal Therapy Sg Koff Et Almentioning
confidence: 99%
“…In keeping with the above, the definition of pure antagonists is further challenged by the observation that these compounds can induce de novo nuclear AR synthesis (Steinsapir et al, 1991) and a sustained decline in prostatespecific antigen levels after their discontinuation (Kelly & Scher, 1993). The anti-tumour efficacy of nilutamide at a lower dose (300mg daily for 1 month followed by 150mg thereafter) was recently evaluated in combination with orchiectomy in a randomised double-blind trial (Janknegt et al, 1993). Among the reported adverse effects, anaemia was observed in 4% of nilutamide-treated patients compared with 7% of placebo patients.…”
Section: Resultsmentioning
confidence: 99%
“…11 The most frequently reported adverse events were nausea and vomiting in 83 patients (11%) followed by hot¯ushes in 74 patients (10%) and eye disorders (total of light/dark adaptation and visual disturbances; 57 patients (8%)). Liver function disturbances and respiratory complaints have been reported as well but less than in other clinical studies.…”
Section: Discussionmentioning
confidence: 96%